Pengaruh Sharia Compliance dan Citra BMT Terhadap Kepuasan Anggota Baitul Mal Wat Tamwil: Studi Kasus Di BMT Arta Bina Serang - Maliatul Husna; Muhamad Rizal Kurnia (Universitas Nusantara PGRI Kediri, 2022)
This study aims to analyze the effect of Sharia Compliance and BMT Image on the satisfaction of BMT Arta Bina Serang members. This research is quantitative descriptive. The population in this study were members of BMT Arta Bina Serang as many as 105 respondents. Sampling used is nonprobability sampling with the technique taken is saturated sampling (census). The researcher gave questionnaires to the respondents and processed the data using the SPSS Version 26 application. The results of this study showed that partially the independent variable had a positive and significant effect on the dependent variable. This is evidenced by the t-count value of Sharia Compliance (X1) of 2,735 which is greater than t table of 1.983038 with a significance probability value of 0.004 < 0.05, meaning that the Shariah Compliance variable partially has a positive and significant effect on member satisfaction. While the t-count value of BMT Image (X2) is 10.104 which is greater than t table 1.983038 with a significance probability value of 0.007 <0.05, meaning that the BMT Image variable partially has a positive and significant effect on member satisfaction. Based on the test of the coefficient of determination (R2) the effect given by the independent variable on the dependent variable is 0.842. This shows that the influence of variables X1 and X2 simultaneously on variable Y is 84.2%, while the remaining 15.8% is influenced by other variables that are not included in this research model.